A NOVEL APPROACH IN DESIGNING ENTERIC-COATED ANTIPLATELET DRUG FOR BYPASSING STOMACH AND GASTRIC IRRITATION - THIRUMALESH NAIK, SUGALI BANOOTH; PURUSHOTHAMAN, MUNUSWAMY; CHANDRA SEKHAR, KOTHAPALLI BANOOTH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The innovative approach in this investigation is making an enteric-coated acetylsalicylic acid (ASA) for antiplatelet activity using a novel excipient. Methods: A novel methodology used in making ASA tablets for tackling the stomach irritation of ASA, by including Plantago ovata seed mucilage as a tablet binder. ASA compatibility with P. ovata seed mucilage was judged by differential scanning calorimetry (DSC) and Fourier Transform Infrared (FTIR) studies. All tablets were prosecuted for flow properties, physicochemical constraints, and release. Results: The enteric-coated tablets established no interface by FTIR and DSC lessons. All the tablets possessed physicochemical constraints. The ASA showed its opposition to discharge in the stomach (2 h) and errand in a basic buffer (within 45 min). Conclusions: The work revealed that with the help of P. ovata as a tablet binder will resolve the disputes connected to gastric irritation.